Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/cancers13163945
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Invasive Adenocarcinomas among Pure Ground-Glass Nodules Less Than 2 cm in Diameter

Abstract: Benign lesions, atypical adenomatous hyperplasia (AAH), and malignancies such as adenocarcinoma in situ (AIS), minimally invasive adenocarcinoma (MIA), and invasive adenocarcinoma (IA) may feature a pure ground-glass nodule (pGGN) on a thin-slide computed tomography (CT) image. According to the World Health Organization (WHO) classification for lung cancer, the prognosis of patients with IA is worse than those with AIS and MIA. It is relatively risky to perform a core needle biopsy of a pGGN less than 2 cm to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 43 publications
(66 reference statements)
1
17
4
Order By: Relevance
“…The invasiveness of GGNs is closely associated with the size and density of lung nodules. Meng et al (2021) [ 28 ] found that 2D long diameter, 2D short diameter, volume, and mean CT value could be predictive indicators of the differential diagnosis of lung adenocarcinoma, which was similar to prior studies [ 29–31 ]. In our study, the 2D mean diameter, 3D mean diameter, mean CT value, maximum CT value, and volume measured by AI were significantly different among the AAH/AIS, MIA, and IAC groups (all P <0.001), which were basically consistent with the mentioned studies above.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The invasiveness of GGNs is closely associated with the size and density of lung nodules. Meng et al (2021) [ 28 ] found that 2D long diameter, 2D short diameter, volume, and mean CT value could be predictive indicators of the differential diagnosis of lung adenocarcinoma, which was similar to prior studies [ 29–31 ]. In our study, the 2D mean diameter, 3D mean diameter, mean CT value, maximum CT value, and volume measured by AI were significantly different among the AAH/AIS, MIA, and IAC groups (all P <0.001), which were basically consistent with the mentioned studies above.…”
Section: Discussionsupporting
confidence: 73%
“…There are different views on the role of CT signs in differentiating pathological subtypes of lung adenocarcinoma. Hsu et al (2021) [ 29 ] reported there were significant differences between the IAC and the non-IAC with respect to lobulation, air cavity except for location, shape, interface, margin, spiculation, vessel relationship, and pleural retraction. Zhan et al (2019) [ 16 ] found that the IAC groups had a higher frequency of mixed GGNs, bubble-like appearance, spiculation, pleural indentation, different locations, and a lower frequency of clear tumor–lung interface when compared with the AIS-MIA group.…”
Section: Discussionmentioning
confidence: 99%
“…Bronchial cutoff and spiculation sign on CT. cutoff, and vascular cluster, are often indicative of a high degree of malignancy and can therefore be used as predictors of poor prognosis in patients (27)(28)(29)(30)(31). In this study, we revealed that spiculation and bronchial cutoff sign on preoperative CT were independent risk factors for lymph node metastasis.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Although these morphological indicators for differentiating neoplastic and non-neoplastic GGNs were not completely consistent in different studies, it is generally believed that whether the boundary is clear or not is of great value for differentiation. 4 , 10 , 11 …”
Section: Introductionmentioning
confidence: 99%